Plasticizing Poly(lactic acid) using epoxidized palm oil for environmental friendly packaging material - Ali, Fathilah; Anuar, Hazleen; Fakhruldin, Hanan (2015)
Renewable resources can create a platform to substitute petroleum-based polymers through innovative bio-based polymers. Poly(lactic) acid (PLA) is the most reliable biodegradable polymer that can be substitute for the application of petrochemical-polymer. Suitable biodegradable plasticizer was studied to examine the effect of the incorporation of plasticizer on mechanical and thermal properties of PLA. The mechanical properties were determined through three-point flexural test and tensile test. The thermal properties were characterized by using Differential Scanning Calorimetry (DSC). Results revealed that the flexibility of PLA can be achieved by the addition of epoxidized palm oil (EPO) as plasticizer in the polymer. It had been proved that 100:10 PLA/EPO was the most significant ratio for PLA/EPO blend. The reinforcement of EPO increased the tensile stress and elongation at break in fact the plasticizer reduced the glass transition of PLA to obtain flexible film of biopolymer.